2021
DOI: 10.3389/fneur.2021.723776
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Version of the ALS Depression Inventory-12

Abstract: Introduction: Depression is a comorbidity in patients with amyotrophic lateral sclerosis (ALS). However, its diagnosis is challenged by the co-occurrence of a similar frontotemporal (FT) behavioral symptom—i.e., apathy. Moreover, its psychometric evaluation is confounded by motor disabilities. This study aimed at investigating psychometric properties and feasibility of the ALS Depression Inventory (ADI-12), a self-report questionnaire set up for this issue—as measuring mood changes without referring to movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…Moreover, at variance with previous reports [12], the present findings appear not to support the widespread notion of bulbar ALS phenotype being more strongly associated with cognitive impairment [22], since bulbar ALS patients did not differ from any of the other groups. Although caution should be exerted when interpreting the present results due to the small number of bulbar ALS patients included (N = 13), it is worth noting that they are in line with recent ones reporting no differences in FTD-like behavioral alterations between patients showing or not bulbar involvement [20,23].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, at variance with previous reports [12], the present findings appear not to support the widespread notion of bulbar ALS phenotype being more strongly associated with cognitive impairment [22], since bulbar ALS patients did not differ from any of the other groups. Although caution should be exerted when interpreting the present results due to the small number of bulbar ALS patients included (N = 13), it is worth noting that they are in line with recent ones reporting no differences in FTD-like behavioral alterations between patients showing or not bulbar involvement [20,23].…”
Section: Discussionsupporting
confidence: 91%
“…The ECAS-CI adds up and complements the currently available range of disease-specific/-nonspecific, behavioural tools that have been standardized in Italy within the ALS population, namely, the Emotional Lability Questionnaire (ELQ) [16], the Dimensional Apathy Scale [17], the State-and Trait-Anxiety Inventory-Form Y (STAI-Y) [18], the ALS Depression Inventory-12 (ADI-12) [19] and the Beaumont Behavioural Inventory (BBI) [15]. However, at variance with them, the ECAS-CI is less time-consuming, as well as embedded within a full, ALS-specific cognitive and behavioural screener, whose section that assesses cognition has been extensively examined for its clinimetrics and feasibility in Italy, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ALS, depression tends to co-occur with anxiety disorders, among others, and diagnosis is often confused with apathy ( 16 ). A recent study conducted in Scotland found a prevalence of 19.7% of neuropsychiatric disorders in patients with ALS, of which 70% were mood disorders ( 17 ).…”
Section: Depression In Patients With Alsmentioning
confidence: 99%